RESILIENCE, FAMILY FUNCTIONING, SOCIO-EMOTIONAL INTELLIGENCE IN WOMEN ABUSED BY THEIR PARTNER AND WHO ATTEND A SURCO WOMAN EMERGENCY CENTE - UGARRIZA CHÁVEZ, Nelly (2021)
The main objective of the study was to examine the relationships between resilience, family functioning and emotional intelligence in women abused by their partner or ex-partner. The type of research was basic and the design was descriptive and correlational, the sampling was not probabilistic for convenience, selecting a sample of 112 women abused by their partner or couple who attended the Emergency Center Woman, the police stations of the district of Surco and the Legal Office of the Ricardo Palma University. The instruments were administered: the Wagnild and Young Resilience Scale, the Bar Emotional Intelligence Inventory and the Family Familiar Questionnaire, de Epstein, Baldwin, and Bishop, whose validity and reliability was  demonstrated. The most important findings establish positive correlations between emotional intelligence and resilience, corroborating hypothesis 1 of the present study in the sense that women who have been mistreated by their partner or expartner reveal that they possess a sufficient degree of emotional intelligence, which helps them to be resilient, facing adversity to physical and psychological harassmentto which they are exposed, and the conditions of the unfavorable context in which they live.